Results of treatment in ovarian cancer - Valdivia Ponce, Eduardo (2015)
The study of early ovarian cancers, is one of the most important chapters of Gynecology; first, by how often served as their incidence is 3 to 4 percent among malignancies of the female genital tract; secondly for its intricate, difficult and controversial of histopathology and thirdly so depressing, both in early diagnosis difficult, as overlapping of their clinical evolution and the limited therapeutic results.